A novel non-destructive workflow for examining germanium and co-substituents in ZnS - Hayes, Sarah M.; McAleer, Ryan J.; Piatak, Nadine M.; White, Sarah Jane O.; Seal, Robert R. (Frontiers in Earth Science, 2023)
A suite of complementary techniques was used to examine germanium (Ge), a byproduct critical element, and co-substituent trace elements in ZnS and mine wastes from four mineral districts where Ge is, or has been, produced within the United States. This contribution establishes a comprehensive workflow for characterizing Ge and other trace elements, which captures the full heterogeneity of samples through extensive pre-characterization. This process proceeded from optical microscopy, to scanning electron microscopy and cathodoluminescence (CL) imaging, to electron microprobe analysis, prior to synchrotron-based investigations. Utilizing nondestructive techniques enabled reanalysis, which proved essential for verifying observations and validating unexpected results. In cases where the Fe content was < 0.3 wt% in ZnS, CL imaging proved to be an efficient means to qualitatively identify trace element zonation that could then be further explored by other micro-focused techniques. Micro-focused X-ray diffraction was used to map the distribution of the non-cubic ZnS polymorph, whereas micro-focused X-ray fluorescence (μ-XRF) phase mapping distinguished between Ge4+ hosted in primary ZnS and a weathering product, hemimorphite [Zn4Si2O7(OH)2·H2O]. Microprobe data and μ-XRF maps identified spatial relationships among trace elements in ZnS and implied substitutional mechanisms, which were further explored using Ge and copper (Cu) X-ray absorption near-edge spectroscopy (XANES). Both oxidation states of Ge (4+ and 2+) were identified in ZnS along with, almost exclusively, monovalent Cu. However, the relative abundance of Ge oxidation states varied among mineral districts and, sometimes, within samples. Further, bulk XANES measurements typically agreed with micro-focused XANES (μ-XANES) spectra, but unique micro-environments were detected, highlighting the importance of complementary bulk and micro-focused measurements. Some Ge μ-XANES utilized a high energy resolution fluorescence detector, which improved spectral resolution and spectral signal-to-noise ratio. This detector opens new opportunities for exploring byproduct critical elements in complex matrices. Overall, the nondestructive workflow employed here can be extended to other byproduct critical elements to more fully understand fundamental ore enrichment processes, which have practical implications for critical element exploration, resource quantification, and extraction.